556 - The Impact of COVID-19 pandemic on elderly's mental health. (October 2021) - Ferreira, Sofia Ramos; Pereira, Daniela; Firmino, Horácio
Abstract : Background: Since the disease caused by the SARS-Cov-2 virus was declared a pandemic by the World Health Organization, countries around the globe adopted measures of social distancing to limit the spread of the virus. Although social distancingmeasures are essential preventive mechanisms, they can promote feelings of loneliness and influence the onset or exacerbation of psychiatric disorders. Current knowledge about the impact of COVID-19 on mental health - and in particular on mental health of the geriatric population - is still scarce. Research Objective: The present review aimed to analyze the COVID-19 pandemic impact on the elderly´s mental health and to suggest measures that can mitigate this impact. Method: A non-systematic review of the literature, through bibliographic research in Pubmed and Embase databases - using the keywords "COVID-19", "SARS-CoV-2", "Coronavirus", "Aging", "Older adults", "Elderly", "Quarantine" and "Mental health" -was performed. Preliminary results of the ongoing study: The available literature points towards a likely increase in mental disorders as a result of the COVID-19 pandemic. This phenomena may be particularly relevant in the elderly population. Several measures – pharmacological and non-pharmacological – can help to maintain the physical and mental health of the elderly. Conclusion: The COVID-19 pandemic had an important impact in elderly's mental health. This subject should be addressed by profissionals/caregivers and measures tominimize negative consequences are in order.